Local Recall Referenda – Past Fate and Proposed Changes - Danel, Łukasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article presents the history of local referenda that seek to recall local authorities in Poland following political changes. In recent years, Poles have proven willing to turn to local referenda to enforce political accountability of their representatives in local government bodies – especially municipality heads (town or city mayors). This has led to the activation of not only local communities, but also political parties and other civil organisations operating at the local level. In the heat of political struggle, the idea of referenda as a form of direct democracy disappears. In the second part of the article the author wonders whether politicians (even those occupying key positions in the country) harm this manifestation of the development of civil society in Poland. Finally, proposals submitted by the president of Poland B. Komorowski for amending some laws with regard to local recall referenda are analysed.